Planning and execution of joint efforts for vaccination against COVID-19 in the city of Manaus: experience report (Research, Society and Development, 2021)
Objective: This article aims to describe the experience of the planning and execution team of joint efforts for vaccine against COVID-19 in the city of Manaus, Amazonas. Methodology: This is a descriptive study, of the experience report type, grounded and conducted according to Holiday, which establishes steps to systematize experiences. Case report: From the experience in the vaccination campaign against COVID-19, it was possible to perceive the importance of the vaccine for society, in relation to the prevention of the disease and, consequently, the reduction of morbidity and mortality. It is also essential to organize joint efforts for vaccination against COVID-19 and the need for these to be structured effectively and with teamwork. Final Considerations: This experience report demonstrates that to achieve the objectives of these joint efforts, planning and teamwork are necessary, as only in this way was it possible to achieve the established goals and one can continue in constant assertiveness in view of the execution of four joint efforts in the city of Manaus that reached the target of vaccinating the scheduled target audience.